2019
DOI: 10.3390/su11082256
|View full text |Cite
|
Sign up to set email alerts
|

Operating Characteristics of Dockless Bike-Sharing Systems near Metro Stations: Case Study in Nanjing City, China

Abstract: With the growth of dockless bike-sharing (DLBS) systems, the first-and-last mile connection to public transport, such as metro and light railway stations, could be improved. DLBS systems complete the trip chain by connecting metro stations with points of interest and enhance the sustainability of urban transportation. Therefore, it is necessary to understand the trans-shipment characteristics of DLBS systems for metro stations. In this study, we collected data from the Mobike DLBS system in Nanjing City, China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…There is an extensive and still growing body of research about the traditional dock-based bike-sharing [31], but the sustainability performance of new-generation dockless schemes has not been thoroughly examined as of yet [32]. A Dutch study found that station-based business models are well institutionalised but harder to scale up, while the dockless model has the greatest scaling potential if institutional adaptations and geo-fencing technologies are successfully implemented [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is an extensive and still growing body of research about the traditional dock-based bike-sharing [31], but the sustainability performance of new-generation dockless schemes has not been thoroughly examined as of yet [32]. A Dutch study found that station-based business models are well institutionalised but harder to scale up, while the dockless model has the greatest scaling potential if institutional adaptations and geo-fencing technologies are successfully implemented [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Land use characteristics in different areas can have an influence on using shared bikes. Based on bike-sharing data within a specified distance of a metro station, Li et al [16] K-means clustering to analyze usage patterns of DLBS systems for metro stations in Nanjing City, China. The results showed that metro stations were clustered into five types on weekdays and three types on weekends, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of "whether there is a transfer with bus or subway", the coefficient of FFBS is positive while ATTS is opposed. This suggests that FFBS is more suitable to combine with other modes of transportation and it is an effective tool for the "first kilometer" and "last kilometer" in the city [15,40]. By contrast, ATTS is more likely to compete with bus and subway and be used alone because of its characteristic of providing door-to-door service.…”
Section: Resultsmentioning
confidence: 99%